Cyclic prefix reduction for 20.48 Gb/s direct-detection optical OFDM transmission over 2560 km of SSMF - Ghanbarisabagh, Mohammad; Alias, M. Y.; Abdul-Rashid, H. A. (WILEY-BLACKWELL, 2011)
Optical Orthogonal Frequency Division Multiplexing (O-OFDM) provides major advantages in mitigating Group-Velocity Dispersion (GVD) in Single Mode Fiber (SMF). Unfortunately, when the uncompensated long-haul transmission ranges become very large, substantial dispersion is accumulated. Owing to the large accumulated dispersion, the Cyclic Prefix (CP) duration will occupy a substantial fraction of the OFDM frame. This effect sets some limitations on the overall throughput and the spectral efficiency. Moreover, the transmission is inefficient because of the energy wastage contained within the CP. In the case where the CP length is shorter than the Channel Impulse Response (CIR), energy wastage is reduced but the system performance is limited by the Inter Symbol Interference (ISI) and Inter Carrier Interference (ICI). To overcome this problem, a Time Domain Equalizer (TEQ) immediately after the channel is proposed. It can cancel the residual ISI and ICI caused by both the GVD and the CP length being shorter than the CIR. The simulation results show that, using BER of 10-3 as a reference, the system performance improves by 2.69thinspacedB while considering 6-feedforward/5-feedback-weight Decision Feedback TEQ (DF-TEQ) and 2.03?dB while considering 10-tap Least Mean Square TEQ (LMS-TEQ) even though the CP length is shorter than the CIR. This method reduces size of the CP, and consequently the performance of the system will be improved. Copyright (c) 2011 John Wiley & Sons, Ltd.